Incidence and Associated Factors for Hypotension After Spinal Anesthesia during Cesarean Section at Thanyaburi hospital - Sribanpot, Jitpisut (Saraburi Hospital Medical Journal, 2025)
During spinal anesthesia for cesarean section most common complication is hypotension that effects to maternal and fetal circulation. The previous study revealed that many factors associated with incidences of hypotension. A cross sectional study from May 1, 2024 to July 31, 2024 was conducted on 107 patients undergoing cesarean section under spinal anesthesia. Chi-square tests, Fisher’s exact test, T-test, Mann-Whiney U test were used in univariate analysis to compare continuous data and categorical data appropriately. Multivariate logistic regression was reported in Odds Ratios (ORs) and 95% confidence interval. Incidence of hypotension was 57.9 %. The probability of hypotension increase with amount of crystalloid preload >200 ml (adjusted OR = 0.28, 95%CI: 0.11 - 0.76, p-value = 0.013) and Time from spinal block to incision ≥10 min (adjusted OR = 3.84, 95%CI: 1.38 – 10.67, p-value = 0.010). Moreover nausea and vomiting (Crude OR = 3.57, 95%CI: 1.10 - 11.53, p-value = 0.034) was related to hypotension. The present results indicated that the incidence of hypotension after spinal anesthesia for cesarean section increased with amount of crystalloid preload >200 ml and time from spinal block to incision ≥10 min.